Latent infection of Caenorhabditis elegans by Orsay virus induces age-dependent immunity and cross-protection - Victoria G. Castiglioni; Ana Villena-Giménez; Dominik Herek; Antonio González-Sánchez; Christina Toft; Gustavo G. Gómez; Santiago F. Elena (Nature Communications)
Abstract The C. elegans-Orsay virus pathosystem provides a powerful model for investigating the mechanisms that govern viral infection and immunity. Here, we focus on two key aspects of this interaction: the impact of lifelong latent infections and the dynamics of superinfection. By tracking the course of a lifelong infection, we demonstrate that the infection remains latent, with animals maintaining control over viral replication for most of their lifespan. Furthermore, we show that animals previously exposed to the virus can suppress viral replication following a second inoculation, indicative of an acquired immune response. Primary infections led to changes in transcriptomic and small RNA profiles, which varied depending on the developmental stage of the host and the timing of analysis. In contrast, superinfection disrupted multiple sRNA classes. Over time, the ability to control repeated viral reactivations declined, whereas resistance to superinfection was stable, ultimately favoring the primary infecting virus. This phenomenon was dependent on a functional RNA interference pathway.